“Comportamiento agronómico del cultivo de maíz (Zea mays, L), a las aplicaciones de inductores hormonales, en el cantón Babahoyo, Provincia de Los Ríos.” - Riera Chávez, Edgar Efraín (2019)
VIII. SUMMARY Maize is one of the major grasses cultivated globally, as well as being important component in agribusiness, as basic raw material in the formulation of balanced products. In Ecuador this grass does not reach its full performance potential, since it is affected by many factors edafoclimáticos, interfering with your productivity. This study sought to increase the crop yield through applications on inductors hormonal. Took place in the premises of the Faculty of agricultural sciences of the Technical University of Babahoyo, located at km 7.5 via Babahoyo-Montalvo, whose geographical coordinates UTM were X: 668690 E; AND: N. 9801098 The area has a humid tropical climate, with an average temperature of 26 ° C, 88% RH. The statistical design used was a block design completely at random with seven treatments and three replications using the significance of Tukey test at 95% probability for comparisons of treatment means. The products used were: Kelpavan extract maximum Ecklonia SP. + auxins and Flower-tie phosphorus P2O5 + auxins. The conclusions reached were: applying inducing hormonal supplement to the soil and foliar fertilization of maize awarded a synergy positive to the plant's metabolism, which can reveal the agronomic variables evaluated. Agronomic variables such as: plant height, stem diameter, height of load; length of ear; diameter of cob and bloom were stimulated physiologically by applications on inductors hormonal, if compared with the control treatment which had no implementation of these inductors. Root lodging, lodging of stem and cob poorly pollinated not affected by the application of hormonal inductors since there was no statistical significance if it compares it with the witness. Performance also was affected positively by stimulants hormonal excelling among these T6 Flower-tie to doses of 0.75 l / ha, which achieved a yield of 5977.93 kg / ha, which provide a net benefit of $680.61 per hectare. Key words: hormonal; inductors; Applications; cultivation of maize.